Early Postoperative Outcomes of Extremity Tumors During the COVID-19 Era in a Developing Country – Is Limb Salvage a Viable Option? - Lantin, Ma. Loren Josephine; Rosario, Mamer; Chua, John Ricardo; Alomesen, Avelino; Jose, Ma. Lilia Monina; Battad, Geoffrey (Asian Pacific Journal of Cancer Care, 2023)
Background: With advancements in surgical techniques and adjuvant therapies, limb salvage (LS) has replaced amputation as the dominant treatment model for malignancies involving the extremities. But the COVID-19 pandemic has drastically affected cancer care especially in developing countries, with treatment delays possibly leading to a rise in amputations. Due to a lack of consensus regarding the ideal course of treatment for tumors involving the extremities in the current situation, the present study aimed to evaluate perioperative and short- term functional outcomes following LS surgery during the COVID-19 pandemic. Methods: A single-institutional series of 45 patients who underwent surgical resection for extremity tumors and followed for at least 6 weeks after operation were included. We analyzed patients according to whether one had LS or major amputation during surgery, and compared intraoperative blood loss, operative duration, perioperative complication rates, COVID-19 infection rates, and Musculoskeletal Tumor Society (MSTS) scores during last follow-up, between the two groups. Results: The LS group (n=21) had significantly longer operative duration (323 min vs. 214 min, p=.004) but higher MSTS scores (81% vs. 49%, p=.001) than the amputation group (n=24). Intraoperative blood loss (1113 mL vs. 779 mL, p=.46), superficial infection rates (14% vs. 8%, p=.12), and COVID-19 infection rates (14% vs. 29%, p=.23) were similar between the two groups. Conclusion: The authors conclude that LS surgery can be a viable option for treating tumors involving the extremities especially in developing countries in the COVID-19 era.